Molecular mechanism of xylose utilization in a plant growth-promoting bacterium Pseudomonas fluorescens SBW25 : a thesis submitted in partial fulfillment of the requirements for the degree of Doctor of Philosophy in Genetics at Massey University, Auckland, New Zealand - Liu, Yunhao (Massey University, 2015)
𝘗𝘴𝘦𝘶𝘥𝘰𝘮𝘰𝘯𝘢𝘴 𝘧𝘭𝘶𝘰𝘳𝘦𝘴𝘤𝘦𝘯𝘴 SBW25 is a plant growth-promoting bacterium that was originally isolated from the phyllosphere of field-grown sugar beet. It is capable of aggressively colonizing sugar beet and a number of other crops such as wheat, maize and peas, and inhibiting the damping-off disease caused by 𝘗𝘺𝘵𝘩𝘪𝘶𝘮 𝘶𝘭𝘵𝘪𝘮𝘶𝘮. 𝘗. 𝘧𝘭𝘶𝘰𝘳𝘦𝘴𝘤𝘦𝘯𝘴 SBW25 has become an important model organism for studying the molecular interactions between bacteria and plants. Previous promoter-trapping analysis showed that SBW25 elevates expression of over 100 genes in its genome when colonizing sugar beet seedlings. These include a candidate gene for xylose utilization, suggesting that SBW25 colonization may be critically dependent on the presence and catabolism of plant-derived xylose. The overall aim of this project is to unravel the molecular basis of xylose utilization by 𝘗. 𝘧𝘭𝘶𝘰𝘳𝘦𝘴𝘤𝘦𝘯𝘴 SBW25 and demonstrate its ecological significance for bacterial survival in complex plant experiments. Bacterial degradation of xylose is sequentially mediated by two enzymes - an isomerase (XutA) and a xylulokinase (XutB) - with xylulose as an intermediate. 𝘗. 𝘧𝘭𝘶𝘰𝘳𝘦𝘴𝘤𝘦𝘯𝘴 SBW25, though capable of growth on xylose as a sole carbon source, encodes only one degradative enzyme XutA in the xylose utilization (𝘹𝘶𝘵) locus. Here, using site-directed mutagenesis and transcriptional assays I identified two functional xylulokinase-encoding genes (𝘹𝘶𝘵𝘉1 and 𝘹𝘶𝘵𝘉2), and further showed that expression of 𝘹𝘶𝘵𝘉1 is specifically induced by xylose. Surprisingly, the xylose-induced 𝘹𝘶𝘵𝘉1 expression is mediated by the mannitol-responsive regulator MtlR, using xylulose rather than xylose as the direct inducer. In contrast, expression of the 𝘹𝘶𝘵𝘈 operon is regulated by 𝘟𝘶𝘵𝘙 in a xylose- and xylulose-dependent manner. Moreover, the data indicate a complex overlapping cellular responses to xylose and other structurally similar sugars such as mannitol, sorbitol, fructose as well as ribose. Both XutR and MtlR are transcriptional activators of the AraC family, members of which typically use DNA-looping to modulate levels of gene expression. The functionality of XutR has been subjected to detailed genetic and biochemical analyses, including promoter mapping, electrophoretic mobility shift assay (EMSA) and DNase I footprinting assay. My data leads to a XutR regulatory model that does not involve DNA-looping. XutR functions as a dimer, which recognizes two inverted repeat sequences; but binding to one half site is very weak requiring inducer molecules such as xylose for activation. To determine the ecological significance of xylose utilization for bacterial colonization 𝘪𝘯 𝘱𝘭𝘢𝘯𝘵𝘢, a Xut⁻ mutant (Δ𝘹𝘶𝘵𝘈) was subjected to competitive colonization on sugar beet seedlings together with a neutrally marked wild-type strain. Results showed that the Δ𝘹𝘶𝘵𝘈 mutant was significant less competitive than the wild-type strain both in the shoot and the rhizosphere. Together, the data show that xylose utilization is an important trait for 𝘗. 𝘧𝘭𝘶𝘰𝘳𝘦𝘴𝘤𝘦𝘯𝘴 SBW25 to colonize surfaces of plants. It should be noted that xylose can only support slow bacterial growth of 𝘗. 𝘧𝘭𝘶𝘰𝘳𝘦𝘴𝘤𝘦𝘯𝘴 SBW25, and thus it is not the sugar of choice in the presence of other preferred carbon and energy sources such as succinate, glucose and arabinose. The underlying mechanism is called carbon catabolite repression (CCR). CCR has been well studied in 𝘌. 𝘤𝘰𝘭𝘪, where it is mainly mediated by the catabolite-activation protein CAP charged with cAMP. However, CCR still remains elusive for non-enteric bacteria such as 𝘗𝘴𝘦𝘶𝘥𝘰𝘮𝘰𝘯𝘢𝘴. Previous studies in other 𝘗𝘴𝘦𝘶𝘥𝘰𝘮𝘰𝘯𝘢𝘴 species indicate that CCR in 𝘗𝘴𝘦𝘶𝘥𝘰𝘮𝘰𝘯𝘢𝘴 occurs at post-transcriptional levels and involves specific binding of the Crc protein to mRNAs of respective catabolic genes. However, genetic tools suitable for studying post-transcriptional gene expression are lacking, particularly vectors derived from mini-Tn7. Mini-Tn7 vectors possess the advantage of delivering reporter fusions into the chromosome in a site- and orientation-specific manner. To facilitate the study of CCR in 𝘗𝘴𝘦𝘶𝘥𝘰𝘮𝘰𝘯𝘢𝘴, I have successfully constructed and validated a panel of five mini-Tn7 vectors for analysis of post-transcriptional gene expression in 𝘗𝘴𝘦𝘶𝘥𝘰𝘮𝘰𝘯𝘢𝘴. Four vectors allow construction of translational fusions to ß-galactosidase (𝘭𝘢𝘤𝘡), while the fifth is designed for functional analysis of noncoding RNA genes. Translational fusions can be constructed without a functional promoter in the vector or from an inducible promoter of either Pₜₐ𝒸 or P𝒹𝒸ₜₐ. I show that promoterless fusions have value for determining levels of translation, whereas fusions to inducible promoters have utility in the analysis of mRNA-binding factors. Next, a combination of site-directed mutagenesis and gene expression assays were used to identify regulators that are involved in the succinate-mediated repression of the 𝘹𝘶𝘵 operon. Succinate is an intermediate of the tricarboxylic acid (TCA) cycle and it is preferentially used by 𝘗. 𝘧𝘭𝘶𝘰𝘳𝘦𝘴𝘤𝘦𝘯𝘴 SBW25 as a source of carbon and energy. In this work, I have successfully identified the major regulatory components of CCR in 𝘗. 𝘧𝘭𝘶𝘰𝘳𝘦𝘴𝘤𝘦𝘯𝘴 SBW25. These include a two-component signal transduction system CbrAB, two small non-coding RNAs CrcY and CrcZ, and a two-protein complex composed of Crc and Hfq. Results showed that when succinate is present, the Crc/Hfq complex inhibits expression of 𝘹𝘶𝘵 genes via binding of the mRNA transcript; when succinate disappears, CbrAB activates the expression of CrcY and CrcZ, which in turn sequesters the Crc/Hfq complex and relieves repression of the 𝘹𝘶𝘵 operon. Taken together, data presented in this thesis indicate novel mechanisms of xylose utilization in terms of not only the catabolic genes but also the mode of their regulation, and reveal complexity and redundancy of regulators involved in the succinate-mediated repression of xylose utilization genes.
Appendix I removed from digital copy for copyright reasons: Liu, J., Rainey, P. B., & Zhang, X.-X. (2014). Mini-Tn7 vectors for studying post-transcriptional gene expression in Pseudomonas. Journal of Microbiological Methods, 107, 182-185. doi.org/10.1016/j.mimet.2014.10.015
Keywords: Pseudomonas fluorescens; Molecular aspects; Research Subject Categories::NATURAL SCIENCES::Biology::Cell and molecular biology::Genetics